Pressure-Relief Mechanism and Application of Large-Diameter Boreholes in Coal Seams with Rockburst Hazard - Zhen Hao; Guangzhong Sun; Haihang Wei; Jiayu Liu; Maolin Tian; Shuaiyi Liu; Yikun Xu (Geofluids)
Drilling of large-diameter boreholes is regarded as an effective measure for rockburst prevention. By investigating the morphological characteristic and evolution of plastic zone in borehole surrounding rock, the pressure-relief mechanism of large-diameter borehole was ascertained, and the engineering application of large-diameter boreholes was assessed in the 13230 working face of Gengcun Coal Mine, Henan Province, China. The results showed that (1) the plastic zone in surrounding rock of borehole appear as circular, elliptical, and butterfly shapes, in which the maximum size of the butterfly wings of the plastic zone is several times larger than the borehole diameter; (2) under certain stress conditions, multiple large-diameter boreholes distributed in coal seam with rockburst risk lead to the generation and coalescence of large-range butterfly-shape plastic zone. They reduce the stress concentration and capacity for storing elastic energy of coal seam, thus reducing the rockburst risk of the coal seam; (3) large-diameter boreholes significantly decrease the stress concentration in front of the 13230 working face and improve the stress environment in the head entry, promoting the safe mining of the working face.